TIRZEPATIDE AND METABOLIC TREATMENT OF OBSTRUCTIVE SLEEP APNEA IN OBESE PATIENTS - EMERGING THERAPEUTIC PERSPECTIVES - Dubaj, Magdalena; Piech, Bartosz; Kubicz Mzabi, Sabina; Judzińska, Alicja; Ignarska, Justyna; Trojanowska, Emilia; Sobczyńska, Kamila; Terbosh, Magda; Osipowska, Julia; Kwolek, Marlena (International Journal of Innovative Technologies in Social Science, 2026)
Obstructive sleep apnea (OSA) is a highly prevalent and underdiagnosed sleep-related breathing disorder characterized by recurrent upper airway obstruction during sleep, leading to intermittent hypoxia and sleep fragmentation. Its incidence continues to rise in parallel with the global obesity epidemic, which represents the most significant modifiable risk factor for OSA. While continuous positive airway pressure remains the gold standard of symptomatic treatment, long-term adherence is often suboptimal, highlighting the need for alternative, disease-modifying therapeutic strategies. This paper explores the role of incretin-based therapies, particularly glucagon-like peptide-1 receptor agonists, focusing mainly on tirzepatide, in the management of OSA. Current evidence suggests that these medications contribute to significant weight reduction, improvement in metabolic parameters, and potential attenuation of OSA severity, as reflected by reductions in the apnea–hypopnea index and hypoxic burden. Beyond weight loss, emerging data indicate that incretin-based therapies may influence key pathophysiological mechanisms of OSA, including systemic inflammation, oxidative stress, and ventilatory control instability. These pleiotropic effects may be particularly relevant in non-obese patients, in whom non-anatomical factors play a predominant role. For these reasons, tirzepatide represents a promising therapeutic approach in the management of OSA.